Prospects of Agrarian Populism and Food Sovereignty Movement in Post-Socialist Romania - Anna Hajdu; Natalia Mamonova (Sociologia Ruralis, 2020)
Progressive agrarian populism and food sovereignty have recently been discussed as having the potential to erode the right-wing populist agitation that is currently widespread in rural areas. However, these ideas are unpopular in post-socialist Eastern Europe. This paper studies the Romanian `new peasant' movement `Eco Ruralis' – a member organisation of La Vía Campesina. It argues that there is a critical mismatch between the progressive objectives of Eco Ruralis and the main worries of villagers in Romania. It also demonstrates the ways in which communist legacies influence societal attitudes towards capitalism and socialism, making the adoption of La Vía Campesina's anti-capitalist and pro-socialist ideologies problematic. Finally, it shows that the concept of `food sovereignty' can be misleading, as this concept is alien to the Romanian countryside. Instead, we reveal that other sustainable practices, such as seed sovereignty, are more culturally appropriate and may play an important role in eroding right-wing sentiments in the countryside.
Keywords: 330; agrarian populist movements; Eastern Europe; food sovereignty; La Vía Campesina; right-wing populism; social movements